Syntheses and crystal structures of lutetium(III) and dysprosium(III) coordination polymers with 2,5-dihydroxybenzene-1,4-dicarboxylate anion: Magnetic and photoluminescent properties of the dysprosium complex - Hussain, Sajjad; Ahmad, Saeed; Sharif, Shahzad; Alarfaji, Saleh S.; Harrison, William T.A.; Chen, Xuenian (Polyhedron, 2020)
[Display omitted] •Lutetium (III), 1 and dysprosium (III), 2 coordination polymers were synthesized.•Characterized by CHN analysis, IR spectroscopy, TGA-DSC and X-ray crystallography.• 3D MOF encapsulating elongated channels propagating in the [100] direction.•Magnetic susceptibility measurement shows compound 2 obeys the Curie Weiss law. Lutetium(III) and dysprosium(III) coordination polymers containing the 2,5-dihydroxybenzene1,4-dicarboxylate (Dhbdc, C8H4O62−) ligand, [Lu(Dhbdc)1.5(H2O)4]n·nC2H6O·nH2O (1) and [Dy(Dhbdc)1.5(H2O)3.58(C2H6O)0.42]n·nC2H6O·0.42nH2O (2) have been prepared from a mixed solvent system and characterized by elemental analysis, infrared spectroscopy, TGA–DSC and X-ray crystallography. The crystal structural analysis reveals that 1 and 2 are almost isostructural, differing slightly in the coordination of the solvent molecules to the respective metal ions. The coordination polyhedra around the metal atoms in 1 and 2 can be described as distorted LnO8 triangular dodecahedra. The structures of the complexes are extended into three-dimensional metal-organic frameworks encapsulating elongated channels propagating in the [100] direction. In both compounds, OH…O hydrogen bonds arising from the coordinated water and solvent molecules help to consolidate the structures. Magnetic susceptibility (χm) measurements were carried out for complex 2, which was found to obey the Curie Weiss law. Luminescent studies of complex 2 indicate that it displays enhanced ligand-centred fluorescence.